2012
DOI: 10.2174/138920112800958788
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Oncogenic Cell Signaling Machinery as a Target for Oncolytic Viruses

Abstract: Viruses function in close harmony with the signaling machinery of their host. Upon exposure to the cell, a battery of viral products become engaged in boosting friendly signaling elements of the host or suppressing harmful ones. The efficiency of viral replication is indeed the biological outcome of this interaction between cellular and host signaling molecules. Oncolytic viruses, natural or man-made, follow the same set of rules of engagement. Pro-oncogenic cell signaling machinery, therefore, is undoubtedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Oncolytic virus therapy is based on the ability of viruses to effectively infect and kill tumor cells without harming the normal tissues. While some viruses seem to have a natural preference for tumor cells, most viruses require the modification in their tropism to specifically enter and/or replicate in cancer cells . Permissiveness of cells to reovirus (a RNA oncolytic virus currently in advanced clinical trials ) has been shown to be dependent on RalA signaling .…”
Section: Oncolytic Viruses and Ral Signalingmentioning
confidence: 99%
“…Oncolytic virus therapy is based on the ability of viruses to effectively infect and kill tumor cells without harming the normal tissues. While some viruses seem to have a natural preference for tumor cells, most viruses require the modification in their tropism to specifically enter and/or replicate in cancer cells . Permissiveness of cells to reovirus (a RNA oncolytic virus currently in advanced clinical trials ) has been shown to be dependent on RalA signaling .…”
Section: Oncolytic Viruses and Ral Signalingmentioning
confidence: 99%
“…1), where CT-26 cells were found to be more sensitive for viral infection and permissive for viral replication than 4T1 cells, even though uPAR expression was similar between the two cell lines. These findings may reflect differences in cellular innate antiviral responses, or in oncogenic pathways , which may render some cancer cells less sensitive to the cytotoxic effects of oncolytic viruses (38, 39). The in vitro and in vivo differences in sensitivity to MV-m-uPA between the two models (which grow in the same mouse strains -(Balb/c-), offer the opportunity to investigate mechanisms of intrinsic resistance to this and other oncolytic measles viruses, and identify strategies to improve the virus' in vitro and in vivo antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…These viruses replicate conditionally in cancer cells leading to their destruction [33][34][35]. Oncolytic virus therapy is based on the ability of natural or mutant viruses to effectively infect and kill tumor cells while sparing normal cells [36][37][38][39][40][41]. Our team has gained a significant level of expertise in the development and evaluation of oncolytic viruses [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Oncolytic virus therapy is based on the ability of natural or mutant viruses to effectively infect and kill tumor cells while sparing normal cells [36][37][38][39][40][41]. Our team has gained a significant level of expertise in the development and evaluation of oncolytic viruses [38][39][40][41][42]. Some oncolytic viruses, while not rationally designed for this purpose, have previously been claimed to preferentially target CSCs [35,43].…”
Section: Introductionmentioning
confidence: 99%